Rare Disease: Cardiac Risk Assessment With MRI in Patients With Myotonic Dystrophy Type 1 - Alì, Marco; Monti, Caterina Beatrice; Melazzini, Luca; Cardani, Rosanna; Fossati, Barbara; Cavalli, Michele; Chow, Kelvin; Secchi, Francesco; Meola, Giovanni; Sardanelli, Francesco (Frontiers in Neurology, 2020)
Introduction: To evaluate myocardial strain and extracellular volume in myotonic dystrophy type I (DM1) patients as potential imaging biomarkers of subclinical cardiac pathology. Materials and methods: We retrospectively analysed 9 DM1 patients without apparent cardiac disease who had undergone cardiac magnetic resonance at our center. Patients were age- and sex-matched with healthy controls. The Mann-Whitney U test was used to compare cardiac strain between the two groups. The t-test was used to compare the ECV obtained in DM1 patients with that in healthy subject. Spearman’s ρ was used for studying the associations among imaging parameters. Results: Global cardiac strain (-19.1%;-20.5%,-16.5%) in DM1 patients was lower (p=0.011) than that in controls (-21.7%;-22.7%,-21.3%). Global extracellular volume in DM1 patients (32.3%;29.3%,36.8%) was also significantly (p=0.008) lower than that reported in literature in healthy subjects (25.6%;19.9%,31.9%). Global cardiac strain showed a strong, positive correlation with septal strain (ρ=0.767, p=0.016) and with both global (ρ=0.733 p=0.025) and septal extracellular volume (ρ=0.767, p=0.016). Discussion: The increase in cardiac extracellular volume and decrease in strain are signs of early cardiac pathology in DM1. Physicians dealing with DM1 may take into consideration cardiac magnetic resonance as a screening tool to identify early cardiac involvement in this condition.